Peran Penting Program Pendidikan Dan Pelatihan Kerja Terhadap Produktivitas Karyawan Bagian Research And Development Di PT. Intera Lesatri Polimer Balaraja - Yana Mulyana; Adam Shaleh; Ibah Misbah (BADAN PENERBIT STIEPARI PRESS, 2021)
Training and education is an activity or business that has the aim and objective of increasing employee productivity, in terms of improving and developing employee knowledge, skills, expertise and attitudes in carrying out their duties and responsibilities. Training and education is carried out after the recruitment of new employees or existing employees who still need education and retraining. In its implementation, training and education for employees is a short-term development program using systematic and organized procedures created to improve work productivity. Good work productivity can open up opportunities for career advancement. Apart from that, with training and work education, it is hoped that it can produce output and quality standards that meet expectations. This research uses a qualitative approach with theoretical studies from previous research. The results of the study found that work training and education can improve the quality of work productivity. Based on the description above, in this research the author will discuss the important role of education and job training programs on the productivity of R&D employees at PT Intera Semut Polymer Balaraja.